Feminist frontiers - Richardson, Laurel; Taylor, Verta A.; Whittier, Nancy (Boston, Mass : McGraw Hill, 2001)
Offers analyses of the causes and consequences of gender inequality and introduces students to feminist theory and methodology
Includes bibliographical references.
Keywords: Feminism -- United States; Women -- United States; Sex role -- United States; Women -- Cross-cultural studies